Pengaruh Social Media Engagement dan Digital Storytelling Terhadap Emosi Pelanggan Tomoro Coffee - Sonia Sinaga; Vika Lestari; Bobby Hartanto; Willy Cahyadi (CV. ITTC INDONESIA, 2026)
The coffee shop industry in Indonesia is experiencing rapid growth, urging business players to adopt innovative digital marketing strategies to maintain competitiveness amid increasingly intense market rivalry. This study aims to analyze the influence of social media engagement and digital storytelling on customer emotions at Tomoro Coffee Tebing Tinggi branch, both partially and simultaneously. This study employed a quantitative method with purposive sampling technique involving 110 respondents who are customers of Tomoro Coffee Tebing Tinggi branch aged 18–35 years, and data were analyzed using SmartPLS through outer model and inner model assessments. The results show that digital storytelling has a positive and significant effect on customer emotions with a path coefficient of 0.686 and T Statistics value of 6.428, while social media engagement has a positive but insignificant effect on customer emotions with a T Statistics value of 1.950 and P Value of 0.052. Simultaneously, both variables are able to explain 73.5% of the variation in customer emotions as indicated by an R² value of 0.735. This study provides practical implications for coffee shop business players to prioritize authentic and emotional digital storytelling strategies in building connections with customers, particularly in medium-sized cities in Indonesia.